Value of lipopolysaccharide binding protein, interleukin-6 and C-reactive protein as biomarkers of severity in acute diverticulitis: a prospective study - Elsing, Christoph; Ernst, Susanne; Stremmel, Wolfgang (Clinical laboratory, 2012)
BACKGROUND: New biomarkers have the capability to predict severity and outcome of infectious diseases. Lipopolysaccharide binding protein (LBP) and Interleukin 6 (IL-6) were determined as new markers in patients with acute diverticulitis and were compared with standard markers such as C-reactive protein (CRP) and white blood cell count (WBC). - METHODS: CRP, IL-6, WBC and LBP were measured in 38 patients at hospital admission and every second day and after colonoscopy. Multi-slice CT scans, ultrasound and early colonoscopy were performed to confirm diagnosis and to detect complications (perforations, stenosis). - RESULTS: CRP, IL-6 and LBP levels one correlated highly with each other and were equally influenced by antibiotic therapy. WBC changes were unremarkable. Severity of the disease (sealed- or non-perforation) was not reflected by the biomarkers. In non-perforated patients, colonoscopy was performed on day 6 (median) after admission with a success rate of 93%. Sealed-perforated patients were examined on median day 11 with a success rate of 60% (p > 0.001). Failure in all cases was due to sigmoidal stenosis requiring surgery. In a receiver-operating characteristic curve analysis (ROC), LBP on day one performed best in predicting colonic steno-sis with an area under the curve of 0.88 (95% CI 0.73 - 0.03 p < 0.02). - CONCLUSIONS: CRP, IL-6, and LBP can be used to monitor diverticulitis. Initial LBP values in patients with acute diverticulitis may also be usefully in detecting candidates for surgical intervention.